Mangrove ecosystem health on prograding land in Panyipatan Sub-district, South Kalimantan, Indonesia - SUSILAWATI SUSILAWATI; YASINTA NUR SHIBA; ENY DWI PUJAWATI; NORMELA RACHMAWATI; MUFIDAH MUFIDAH; EVA PRIHATININGTYAS (Society for Indonesian Biodiversity, 2026)
Abstract. Susilawati, Shiba YN, Pujawati ED, Rachmawati N, Mufidah, Prihatiningtyas E. 2026. Mangrove ecosystem health on prograding land in Panyipatan Sub-district, South Kalimantan, Indonesia Biodiversitas 27 (1): d270106. https://doi.org/10.13057/biodiv/d270106. Mangrove forests are essential for coastal protection and climate-change mitigation. This study, conducted in the mangrove forests of Panyipatan Sub-district, South Kalimantan, Indonesia, assessed community structure, Importance Value Index (IVI), species diversity (H′), and vegetation damage across two tidal zones using 50×100 m plots and the Forest Health Monitoring (FHM). In Zone 1, Avicennia marina dominated with an IVI of 147.92%, followed by Excoecaria agallocha with an IVI of 183.08%. In Zone 2, the dominance of E. agallocha increased markedly, reaching IVI values of 279.49% for saplings and 226.11% for trees, accompanied by Cerbera manghas (IVI 19.47%). Species diversity varied between zones: sapling diversity was lower in Zone 1 (H′ = 0.69) despite more individuals, while Zone 2 showed higher sapling diversity (H′ = 0.95) with fewer individuals. Tree‐level diversity was similar between zones (0.67 vs. 0.64). Vegetation damage was dominated by leaf damage (35%) and liana infestation (43%), mostly of moderate severity, with the Area Damage Index (ADI) categorized as low (5.37-5.00). These results highlight the link between species dominance and diversity, as well as the influence of growth‐stage diversity on vegetation health. Management priorities include strengthening pioneer species, controlling lianas, applying adaptive rehabilitation, and enhancing collaboration between communities and government to sustain mangrove ecosystems under shifting coastlines.